2021
DOI: 10.20452/pamw.16041
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular manifestations in obstructive sleep apnea: current evidence and potential mechanisms

Abstract: as nonrestorative sleep and excessive daytime sleepiness (EDS). 7,8In addition to EDS, OSA is associated with reduced quality of life, poor cognitive function, and road traffic accidents, independent of age or sex. 9 -11 The principal morbidity and mortality of the condition, however, are due to the increased risk of the development and progression of numerous CVDs. 4 A large body of evidence has accumulated to date strengthening the association between OSA and CVD, with increased risk persisting after corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 101 publications
(121 reference statements)
2
12
0
1
Order By: Relevance
“…In addition, severe and moderate OSAS has been related to poor CAD prognosis, deteriorated sleep-related symptoms, and impaired sleep-related quality of life [ 30 , 31 ]. In accordance with previous studies, our findings also showed that CCS patients with moderate to severe OSAS were more vulnerable to diabetes mellitus, obesity, hyperlipidemia, and more severe inflammatory response [ 30 34 ]. Although OSAS is a well-documented risk for adverse cardiovascular outcomes [ 6 , 13 , 30 34 ], few studies have evaluated the polysomnographic feature of hospitalized CCS patients in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, severe and moderate OSAS has been related to poor CAD prognosis, deteriorated sleep-related symptoms, and impaired sleep-related quality of life [ 30 , 31 ]. In accordance with previous studies, our findings also showed that CCS patients with moderate to severe OSAS were more vulnerable to diabetes mellitus, obesity, hyperlipidemia, and more severe inflammatory response [ 30 34 ]. Although OSAS is a well-documented risk for adverse cardiovascular outcomes [ 6 , 13 , 30 34 ], few studies have evaluated the polysomnographic feature of hospitalized CCS patients in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Along with recurrent episodes of complete or partial nocturnal breathing interruption, pathophysiologic alterations are known to occur in OSA patients, including hypertension, congestive heart failure, coronary artery disease, episodic hypoxemia, insulin resistance, and neurocognitive dysfunction [ 2 ]. OSA has been identified as an independent risk element for cardiovascular diseases [ 3 ]. Chronic intermittent hypoxia (CIH) is a key factor in OSAHS causing cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, anomalies in the oxidative stress system have been linked to endoplasmic reticulum stress. High-level oxidative stress in the endoplasmic reticulum harasses the healthy functioning of cells, causing various heart diseases such as cardiac hypertrophy, myocardial infarction, cardiac insufficiency, and heart failure [ 3 , 6 ]. The extensive clinical and animal experiments have expounded that OSA induces an increase in the ratio of heart weight : body weight (HW : BW) and enhances the levels of plasma atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), and angiotensin II (An g II) [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…OSA adversely alters the cardiovascular structure, inducing changes such as endothelial dysfunction. Additionally, OSA is reported as an independent risk factor for initiation or progression of cardiovascular diseases like hypertension, heart failure, ischemic heart disease, and stroke ( Marin et al, 2005 ; Bradley and Floras, 2009 ; Wang et al, 2013 ; Orrù et al, 2020 ; Chen et al, 2021 ; O’Donnell et al, 2021 ). The treatment of OSA includes continuous positive airway pressure (CPAP) and mandibular advancement devices (MAD), but there is no effective drug therapy for OSA.…”
Section: Hypoxia and Cardiovascular Diseasesmentioning
confidence: 99%
“…CPAP and MAD keep the upper airway open during sleep. It has been suggested that CPAP and MAD therapies attenuate some cardiovascular diseases including atherosclerosis, hypertension, heart failure, and cardiac arrhythmias ( Barnes et al, 2004 ; Gotsopoulos et al, 2004 ; Bradley and Floras, 2009 ; Marklund et al, 2019 ; Yamamoto et al, 2019 ; Chen et al, 2021 ; O’Donnell et al, 2021 ).…”
Section: Hypoxia and Cardiovascular Diseasesmentioning
confidence: 99%